2021
DOI: 10.1177/23259671211009846
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Rotator Cuff Tears and Superior Migration of the Humeral Head: An MRI-Based Anatomic Study

Abstract: Background: Superior humeral migration has been established as a component of rotator cuff disease, as it disrupts normal glenohumeral kinematics. Decreased acromiohumeral interval (AHI) as measured on radiographs has been used to indicate rotator cuff tendinopathy. Currently, the data are mixed regarding the specific rotator cuff pathology that contributes the most to humeral head migration. Purpose: To determine the relationship between severity of rotator cuff tears (RCTs) and AHI via a large sample of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This inconsistency among the readers is most probably due to the difficulties to identify the landmarks for Deutsch and Moloney as stated above. The finding of a reduced ACHD in shoulders with rotator cuff tear was well expected and has been shown in many studies [23][24][25][26]. As a further refinement, our data strongly suggest that an ACHD ≤ 6 mm is a realistic threshold to infer a rotator cuff pathology since all of the 152 control shoulders had an ACHD of ≥ 7 mm.…”
Section: Discussionsupporting
confidence: 86%
“…This inconsistency among the readers is most probably due to the difficulties to identify the landmarks for Deutsch and Moloney as stated above. The finding of a reduced ACHD in shoulders with rotator cuff tear was well expected and has been shown in many studies [23][24][25][26]. As a further refinement, our data strongly suggest that an ACHD ≤ 6 mm is a realistic threshold to infer a rotator cuff pathology since all of the 152 control shoulders had an ACHD of ≥ 7 mm.…”
Section: Discussionsupporting
confidence: 86%
“…Narrowing of the AHI, indicating superior migration of the humeral head, was thought to reflect the presence of rotator cuff tears, especially multiple-tendon rotator cuff tears involving the ISP. 17,20 In a previous study, patients with massive rotator cuff tears and a reduced range of motion in elevation and ER had a significantly narrower AHI than did patients with massive rotator cuff tears without a reduction in the range of motion. 2 The underlying mechanism is unknown; however, since the percentage of patients with superior migration of the humeral head increased as the stage of fatty infiltration of the SSP and ISP advanced, 17 superior migration of the humeral head may reflect severe fatty infiltration of the involved muscle and long duration from the onset of tendon rupture, which can explain the reduction of the range of anterior elevation and ER in this study.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent study showed that RC tear causes humeral migration by affecting the dynamic stabilizers of the shoulder [ 21 ]. In addition, about imaging methods to evaluate the displacement of the humeral head in RC tears, they evaluated the benefits of parameters such as upward migration index, inferior glenohumeral distance, acromial index and critical shoulder angle other than AHD.…”
Section: Discussionmentioning
confidence: 99%
“…The higher likelihood of LHBT pathology, with the increasing size of RC tears, may be a consequence of its functioning as a suppressor of the humeral head [ 1 ]. A study showed that any RC tear compromises the dynamic stabilizers of the shoulder and significantly leads to superior humeral migration [ 21 ]. Subacromial impingement may also contribute to LHBT pathology in the presence of an RC tear [ 23 ].…”
Section: Introductionmentioning
confidence: 99%